Welfare effects of commodity price and exchange rate volatilities in a multi-sector small open economy model - Ali Dib (Bank of Canada, 2008)
This paper develops a multi-sector New Keynesian model of a small open economy that includes commodity, manufacturing, non-tradable, and import sectors. Price and wage rigidities are sector specific, modelled à la Calvo-Yun style contracts. Labour and capital are imperfectly mobile across sectors. Commodities, whose prices are exogenously set in world markets and denominated in a foreign currency, are divided between exports and home uses as direct inputs in production of manufactured and non-tradable goods. Structural parameters of monetary policy, wage and price rigidities, capital adjustment costs, and exogenous process shocks are econometrically estimated using Canadian and U.S. data for the period 19812005 and a maximum likelihood procedure. The estimates indicate significant heterogeneity across sectors. The model is then simulated to evaluate the effects of commodity price shocks on real exchange rate variability and to measure their welfare implications, by conducting welfare analysis employing a second-order solution method. The main results show that commodity price shocks, which are shocks to the terms of trade, significantly contribute to exchange rate fluctuations and business cycles in the small open economy. Moreover, because of different non-linearities in the model, fluctuating commodity prices lead to welfare gains when adopting a flexible exchange rate regime. This regime is also required to improve welfare gains and to offset negative effects of other domestic and foreign shocks.
Keywords: E4; E52; F3; F4; 330; Economic models; Exchange rate regimes; International topics; Preisniveau; Wechselkurs; Volatilität; Wohlfahrtseffekt; Kleines-offenes-Land; Kanada; USA